Functional identification and expressional responses of large yellow croaker (Larimichthys crocea) interleukin-8 and its receptor. Issue 87 (April 2019) - Wang, Tianming; Liang, Jing; Xiang, Xiaowei; Yuan, Jiajie; Chen, Xu; Xiang, Xingwei; Yang, Jingwen
Abstract: Interleukin-8 (IL-8 or chemokine (C-X-C motif) ligand 8, CXCL8) is a chemokine produced by multiple cell types. It promotes chemotaxis and phagocytosis via interaction with chemokine receptors CXCR1 and CXCR2. Using published data, IL-8 gene ( LcIL-8 ) of the large yellow croaker ( Larimichthys crocea ) was cloned into the pcDNA3.1 plasmid, and an interleukin-8 receptor ( LcCXCR2 ) was cloned into the pEGFP-N1 plasmid. Secratory expression of Lc IL-8 in HEK293T cells was carried out, and product in culture medium was collected for Lc CXCR2 stimulation in HEK293 cells. Following receptor internalization observation and intracellular signaling detection, the functional interaction of Lc IL-8 and Lc CXCR2 was further determined and the ERK phosphorylation signal activation mediated by Lc CXCR2 was demonstrated. Quantitative real-time PCR analysis was used to analyze transcription level regulation of Lc IL-8 and Lc CXCR2 in various tissues of large yellow croaker. Expression of LcIL-8 and LcCXCR2 was elevated in the spleen, head kidney, and liver after Vibrio parahemolyticus challenge. Results illustrated the functional interaction between Lc IL-8 and Lc CXCR2 in mediating intracellular ERK1/2 phosphorylation signaling and suggested that the Lc IL-8 and Lc CXCR2 system is part of the immune response induced by V. Parahemolyticus in L. crocea . Highlights: The full length CDS of Lc CXCR2 from spleen of large yellow croaker was cloned. The cell surface localization of Lc CXCR2 was determinated. Fusion expression of Lc IL-8 and Lc CXCR2 was conducted in HEK293T and HEK293 cells. The functional inteaction between Lc IL-8 and Lc CXCR2 was demonstrated and their immunoregulatory function has been revealed.